PERENCANAAN REAKTIVASI JALAN REL KERETA API KORIDOR MAGELANG – AMBARAWA - Rizqi Nugroho; Giovanny Natasha F. P.; Moga Narayudha; Bambang Pudjianto (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
Highway Traffic on Semarang – Magelang track was having a significant increased of traffic flow, the degree saturation of highways and travel time, and decreased of vehicle speed. An alternative is required to overcome conditions. In accordance with the Railways Master Plan of Central Java Province, for Semarang – Magelang track, the railway corridor Magelang – Ambarawa is one of the reactivation form of the non active railway. Feasibility study of railway reactivation of Semarang – Magelang track in 2013, potential train passengers by 2038 pnp/day, the potential for freight transport by 7.7 tons/day and supported by the existing of rail way which can be reactivated. Based on topography with the avarage flatness is 20 o/oo, there are 3 alternatives for railway track that was developed with the utilization of existing track along 21.9 km and selected alternative track along 13,1 km. From the result of potential analysis of the passanger and existing condition are using grade 4th for railway grade plans with overall planning is based on the previsons of PM No. 60 in 2012, KM. No. 52 in 2000, and PD PJKA No. 10 in 1986.